2022
DOI: 10.1039/d2nj02469a
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic actions of phytonutrient capped nanosilver as a novel broad-spectrum antimicrobial agent: unveiling the antibacterial effectiveness and bactericidal mechanism

Abstract: Nanosilver is a versatile biomedical agent that can potentially battle against bacterial infection. Herein, we introduce an energy-efficient green approach to synthesize phytonutrients modified silver nanoparticles (AgNPs) using cogon grass...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The presence of phytochemicals, such as phenolic compounds, flavonoids, alkaloids, glycosides, terpenoids, amino acid residues, and proteins, are considered to be the factors responsible for reducing silver ions by HC extract [47]. Generally, phenolic compounds are responsible for the reduction of Ag + ions to Ag atoms, which leads to the formation of AgNPs [24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The presence of phytochemicals, such as phenolic compounds, flavonoids, alkaloids, glycosides, terpenoids, amino acid residues, and proteins, are considered to be the factors responsible for reducing silver ions by HC extract [47]. Generally, phenolic compounds are responsible for the reduction of Ag + ions to Ag atoms, which leads to the formation of AgNPs [24].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the influence of silver nanomaterials on bacterial cells and the production of ROS in bacterial cells were also examined. The experimental finding revealed that HCE-AgNPs induce oxidative stress by damaging the cell wall, ultimately resulting in cell death [24,51]. Additionally, ATP, which is involved in the metabolism of cellular energy, was reduced due to the remarkable inhibition by the AgNPs, causing bacterial apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The generation of reactive oxygen species (ROS) is also considered one of the mechanisms underlying the antimicrobial activity of AgNPs. AgNPs and Ag + contribute to the production of hydroxyl radicals and ROS, thereby increasing the levels of cellular ROS and inhibiting bacterial cell growth [53]. The denaturation of DNA is also associated with ROS production, as oxidative damage to amino acids caused by oxygen radicals associated with AgNPs and Ag + ion exposure can disrupt the protein structure [54].…”
Section: Analysis Of Potential Antimicrobial Activity 241 Mbc and Mic...mentioning
confidence: 99%